2019
DOI: 10.12681/hnps.1804
|View full text |Cite
|
Sign up to set email alerts
|

Nucleon numbers for nuclei with shape coexistence

Abstract: We consider two competing sets of nuclear magic numbers, namely the harmonic oscillator (HO) set (2, 8, 20, 40, 70, 112, 168, 240,...) and the set corresponding to the proxy-SU(3) scheme, possessing shells 0-2, 2-4, 6-12, 14-26, 28-48, 50-80, 82-124, 126-182, 184-256... The two sets provide 0 + bands with different deformation and bandhead energies. We show that for proton (neutron) numbers starting from the regions where the quadrupole-quadrupole (Q · Q) interaction, as derived by the HO, becomes weaker than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…It was suggested [225,228,229] that the interplay between HO and SO magic numbers offers a simple justification for the appearance of islands of SC on the nuclear chart. Let us see how this is occurring.…”
Section: A Dual Shell Mechanism For Shape Coexistencementioning
confidence: 99%
“…It was suggested [225,228,229] that the interplay between HO and SO magic numbers offers a simple justification for the appearance of islands of SC on the nuclear chart. Let us see how this is occurring.…”
Section: A Dual Shell Mechanism For Shape Coexistencementioning
confidence: 99%
“…In section II we have argued, that the intrinsic singleparticle basis for the valence shell of deformed nuclei within the Elliott SU(3) symmetry is the cartesian basis |n z , n x , n y , m s , because such orbitals are eigenstates of the dominant q 0,i q 0,i interaction [82] and due to the fact, that rotational nuclear bands emerge from these states [35,36]. In addition in section II in Eqs.…”
Section: Particle Excitationsmentioning
confidence: 99%
“…For instance, when the particles are in the 6-14 SO-like shell, the previously filled orbitals 1s 1/2 , 1p 3/2 create a closed core, if one uses the proxy-SU(3) symmetry [39] (see Table I of Ref. [82]) and thus no hole irreps emerge. This is actually a difference of the dual-shell mechanism with the particle-hole mechanism as realized in the Symplectic Model [68,[91][92][93].…”
mentioning
confidence: 99%
“…Lately, it has been observed that in areas where shape coexistence [9] is expected, the ground state band and the nearby lying K = 0 band are represented by the proxy-SU(3) irreps and the exact SU(3) irreps occurring by consideration of the magic numbers of the isotropic three-dimensional harmonic oscillator [10,11].…”
Section: Proxy-su(3) and Shape Coexistencementioning
confidence: 99%